A case reported with 46, XX testicular disorders of sexual development and its possible association with dysembryoplastic neuroepithelial tumour - Furqan, Saira; Muhammad Waleed; Arif Maan , Soban; Sumera Batool; Naeemul Haque (Journal of the Pakistan Medical Association, 2023)
The main factor determining differentiation of bipotential gonads into testes or ovaries is the presence or absence of SRY (sex-determining region on Y chromosome) gene. De la Chapelle syndrome is a chromosomal anomaly with chromosomal makeup of a female (46, XX) and phenotypic presentation of a male. Previously known as XX sex reversal, it is now called 46, XX testicular disorders of sexual development (DSD). Although rare, it presents as a major chromosomal anomaly, with SRY gene crossover proposed as an underlying aetiology in most patients. We report the case of a 25-year-old male who presented with infertility and was diagnosed with De 46, XX testicular DSD. He has a previous history of resected dysembryoplastic neuroepithelial tumour (DNT). The differential diagnosis of 46, XX DSD and possible association/coincidental finding of DNT have been discussed. ---Continue